2020
DOI: 10.1111/ijd.15331
|View full text |Cite
|
Sign up to set email alerts
|

Acne keloidalis nuchae and thyroid diseases: a population‐based cohort study

Abstract: Background The association between acne keloidalis nuchae (AKN) and thyroid diseases is yet to be investigated. Objective To evaluate the risk of developing hypothyroidism and hyperthyroidism among patients with AKN and to characterize the patients who have AKN and thyroid comorbidities. Methods A population‐based cohort study was conducted comparing AKN patients (n = 2,677) with age‐, gender‐, and ethnicity‐matched control subjects (n = 13,190) with regard to incident cases of hypothyroidism and hyperthyroidi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Regarding diabetes, insulin resistance has been implicated in the pathogenesis of AKN [4,14]. Patients with AKN are also much more likely to develop new-onset hypothyroidism, which may be driven by a change in autoimmunity related to the pathogenesis of AKN [26].…”
Section: Resultsmentioning
confidence: 99%
“…Regarding diabetes, insulin resistance has been implicated in the pathogenesis of AKN [4,14]. Patients with AKN are also much more likely to develop new-onset hypothyroidism, which may be driven by a change in autoimmunity related to the pathogenesis of AKN [26].…”
Section: Resultsmentioning
confidence: 99%
“…The greater dominance of females among patients with AKN and thyroid diseases aligns with the general female preponderance in thyroid diseases and autoimmune thyroid disease, in particular. No association between AKN and hyperthyroidism was found [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Autoimmune thyroiditis, also known as Hashimoto thyroiditis, is an autoimmune disease that destroys thyroid cells by cell and antibody-mediated immune processes [ 13 ]. A study by Valdman-Grinshpoun et al demonstrated an increased risk of hypothyroidism among female patients with AKN [ 14 ]. The higher prevalence of females among individuals with AKN and thyroid diseases corresponds with the typical female predominance observed in thyroid diseases, particularly autoimmune thyroid disease.…”
Section: Introductionmentioning
confidence: 99%